Thymic Polypeptide Fraction Biomodulina T Decreases Exhausted and Terminally Differentiated EMRA T Cells in Advanced Lung Cancer Patients Treated With Platinum-Based Chemotherapy - Suárez, Gisela María; Catalá, Mauricio; Peña, Yadira; Portela, Susana; Añé-Kourí, Ana Laura; González, Amnely; Lorenzo-Luaces, Patricia; Díaz, Manuel; Molina, María de los A.; Pereira, Karla; Hernández, Jenysbel de la C.; Ramos, Raúl; et al. (Frontiers in Oncology, 2022)
Lung cancer is the second cause of cancer related deaths worldwide. Chemotherapy and immunotherapy represent the current standard of care for advanced NSCLC. Platinum-based chemotherapy expands late-differentiated T cell populations. Therefore, immune restoration after chemotherapy to adjuvate the immunotherapeutic potential could be crucial. The aim of this study was to evaluate the effect of Biomodulina T (BT), a thymic polypeptide fraction, on peripheral lymphocytes subpopulations in the context of cancer disease. Additionally, whether these effects might induce a better response to CIMAvax-EGF, an epidermal growth factor (EGF) depleting immunotherapy. Eighteen advanced NSCLC patients were evaluated after being treated with platinum-based chemotherapy. We found that the frequency of terminally differentiated effector T cells re-expressing CD45RA (EMRA) CD4+ (p=0.0031) and CD8+ (p=0.0372) T cells decreased with the administration of BT, whereas CD4+ naive T cells increase in more than 70% of the patients. Remarkably, CD4+ and CD8+ T lymphocytes expressing programmed cell death receptor-1 (PD1) significantly decreased after BT administration (p=0.0005 and p<0.0001, respectively). We also found an enhancement of the anti-EGF antibody response with a large percentage of patients treated with CIMAvax-EGF reaching the good antibody response condition after four vaccine doses. Moreover, the median overall survival of patients treated with CIMAvax-EGF was 16.09 months. In conclusion, our results suggest that the immunorestoration generated by the administration of BT after first-line chemotherapy may induce a better immune response to CIMAvax-EGF that could translate into the clinical benefit of patients diagnosed with advanced NSCLC.